2021
DOI: 10.1080/21655979.2021.1972080
|View full text |Cite
|
Sign up to set email alerts
|

Centromere protein E as a novel biomarker and potential therapeutic target for retinoblastoma

Abstract: Retinoblastoma is the most common intraocular malignancy during childhood. Currently, there is no effective treatment for metastatic retinoblastoma. We investigated potential biomarkers of retinoblastoma by utilizing three datasets from a public database. Functional enrichment analysis, including gene ontology, Kyoto encyclopedia of genes and genomes, gene set enrichment analysis and variation analysis, suggested that differentially expressed genes in retinoblastoma were enriched in accelerated cell cycle even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Since the prognostic role of infiltrating immune cells have been proposed across many human cancers ( Gentles et al, 2015 ), we pay attention to the link between glioma immunity and CENP-A in this research. Several research models regarding centromeric factor in cancer proposed the association with immune infiltration ( Shi et al, 2021 ; Zeng et al, 2021 ; Zhou et al, 2021 ). We also showed that CENP-A expression level was associated with the level of infiltrating immune cells in gliomas and presented the strongest correlation with Th2 cells and pDCs.…”
Section: Discussionmentioning
confidence: 99%
“…Since the prognostic role of infiltrating immune cells have been proposed across many human cancers ( Gentles et al, 2015 ), we pay attention to the link between glioma immunity and CENP-A in this research. Several research models regarding centromeric factor in cancer proposed the association with immune infiltration ( Shi et al, 2021 ; Zeng et al, 2021 ; Zhou et al, 2021 ). We also showed that CENP-A expression level was associated with the level of infiltrating immune cells in gliomas and presented the strongest correlation with Th2 cells and pDCs.…”
Section: Discussionmentioning
confidence: 99%
“…It was worth noting that the function of highly expressed CENPE was also enriched in the T cell receptor signaling pathway. It had been reported that high expression of CENPE promoted immune cell infiltration, especially B cells [ 63 ]. Similarly, we also found that CENPE was significantly and positively related to CD8 + T cell and macrophage.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pediatric tumors, this kinase is associated with lower overall survival and EFS rates in EPN [ 344 , 345 ], RMS [ 346 , 347 ] and NB [ 348 ]. In silico analyses have also demonstrated that CDK1 is differentially expressed in RB [ 349 ] and plays a key role in the development of OS, since its negative regulation or depletion leads to significant decreases in proliferation while inducing apoptosis [ 350 , 351 , 352 , 353 ].…”
Section: Protein Kinases In Pediatric Oncology and Their Association ...mentioning
confidence: 99%